The Physical, Psychological, and Social Day-to-Day Experience of Women Living With Endometriosis Compared to Healthy Age-Matched Controls-A Mixed-Methods Study - Elisabeth Olliges; Elisabeth Olliges; Elisabeth Olliges; Alina Bobinger; Annemarie Weber; Verena Hoffmann; Timo Schmitz; Timo Schmitz; Roxana M. Popovici; Roxana M. Popovici; Karin Meissner; Karin Meissner (Frontiers Media S.A., 2021)
Background: Endometriosis is characterized by lesions of endometrial tissue outside the uterus. Chronic pain is considered as main symptom, but challenges can relate to various physical, mental, and social aspects of the women's lives. The aim of our study was to gain a holistic understanding of the everyday reality of women with endometriosis compared to healthy controls.Methods: The total sample comprised 12 hormone-free endometriosis patients (EP) and 11 age-matched healthy women (HC). A mixed-methods design was used comprising semi-structured interviews, standardized questionnaires and a comprehensive diary to assess pain ratings and various mental and physical symptoms over the course of a menstrual cycle. Interviews were recorded, transcribed, and evaluated according to phenomenological analysis using the MAXQDA software.Results: Interviews showed that living with endometriosis was associated with an impairment in everyday life. Physical strains, especially pain, high levels of psychological distress, and social limitations have been reported. Living with endometriosis affected the patients' personality and they "no longer felt like themselves." Physical and psychological symptoms were reported to interfere with social interaction and participation. Evaluation of the standardized questionnaires revealed significant impairments in EP compared to HC in regard to anxiety and depression scores (both p < 0.001; Hospital Anxiety and Depression Scale), mental and physical quality of life (both p < 0.001; Short-Form Health Survey-12), stress ratings (p < 0.001; Patient Health Questionnaire-15) and functional well-being (p < 0.001; Functional Well-being-7). The highest levels of mean pelvic pain and dyschezia were observed in EP during menstruation, but mean pain ratings and dyschezia were increased in EPs compared to HP during the whole cycle. EP reported mental symptoms (e.g., depressed mood or anxiety) mainly during menstruation, while HC did not show any mental symptoms during the cycle. In addition, physical symptoms were elevated during the entire cycle in EPs (all p < 0.01).Discussion: The mixed-methods approach enabled to interpret the interviews, the standardized questionnaires, and the symptom diary in a broader context of everyday life. The symptoms do not appear to act independently, but rather influence each other. This leads to a complex interplay of physical, mental, and social impairments, with pain often being the starting point.